Effect of CQ-amine ratio on the degree of conversion in resin monomers with binary and ternary photoinitiation systems - Ho-Jin Moon; Dong-Hoon Shin (Korean Academy of Conservative Dentistry, 2012)
Objectives This study evaluated the effect of camphorquinone (CQ)-amine ratio on the C=C double bond conversion of resins with binary and ternary photoinitiation systems. Materials and Methods Two monomer mixtures (37.5 Bis-GMA/37.5 Bis-EMA/25 TEGDMA) with binary systems (CQ/DMAEMA in weight ratio, group A [0.5/1.0] and B [1.0/0.5]) and four mixtures with ternary system (CQ/OPPI/DMAEMA, group C [0.1/1.0/0.1], D [0.1/1.0/0.2], E [0.2/1.0/0.1] and F [0.2/1.0/0.2]) were tested: 1 : 2 or 2 : 1 CQ-amine ratio in binary system, while 1 : 1 ratio was added in ternary system. The monomer mixture was cured for 5, 20, 40, and 300 sec with a Demetron 400 curing unit (Demetron). After each exposure time, degree of conversion (DC) was estimated using Fourier transform infrared (FTIR) spectrophotometer (Nicolet 520, Nicolet Instrument Corp.). The results were analyzed by ANOVA followed by Scheffe test, with p = 0.05 as the level of significance. Results DC (%) was expressed in the order of curing time (5, 20, 40, and 300 sec). Group A (14.63 ± 10.42, 25.23 ± 6.32, 51.62 ± 2.69, 68.52 ± 2.77); Group B (4.04 ± 6.23, 16.56 ± 3.38, 37.95 ± 2.79, 64.48 ± 1.21); Group C (16.87 ± 5.72, 55.47 ± 2.75, 60.83 ± 2.07, 68.32 ± 3.31); Group D (23.77 ± 1.64, 61.05 ± 1.82, 65.13 ± 2.09, 71.87 ± 1.17); Group E (28.66 ± 2.92, 56.68 ± 1.33, 60.66 ± 1.17, 68.78 ± 1.30); Group F (39.74 ± 6.31, 61.07 ± 2.58, 64.22 ± 2.29, 69.94 ± 2.15). Conclusion All the monomers with ternary photoinitiation system showed higher DC than the ones with binary system, until 40 sec. Concerning about the effect of CQ-amine ratio on the DC, group A converted into polymer more than group B in binary system. However, there was no significant difference among groups with ternary system, except group C when cured for 5 sec only.